Method for flash evaporation purification of graphite leaching residues of waste lithium batteries
Purify the waste lithium battery graphite leaching slag through flash halogenation and Joule thermal insulation coating technology, and combine it with low-temperature lithium deposition technology to solve the problems of high recycling cost, large energy consumption and introduction of miscellaneous elements in waste lithium battery graphite leaching slag, and realize the problem of high recovery cost, high energy consumption and poor elements. Highly efficient and low-consumption graphite leaching residue recovery and purification.
Patent Information
- Application Number
- CN202411804839.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-02-14
AI Technical Summary
The wet leaching discharge of waste lithium batteries is costly and has high energy consumption. The residual metal recycling process is long and the introduction of miscellaneous elements affects the purity and utilization of graphite.
The flash halogenation technology is used to mix the waste lithium battery graphite leaching slag with the halogenating agent, and the flickering treatment is carried out under high temperature and high pressure conditions to separate solid-phase purified graphite and gas-phase metal flash vapor. Subsequently, the surface kinetic energy generated in Joule thermal insulation state is pushed to coat the surface of the purified graphite particles, and the lithium element is purified by low-temperature deposition of lithium technology.
The efficient purification of graphite leaching slag was achieved, with graphite purity reaching 99.7%, and lithium carbonate purity reaching 99.5%, avoiding the emission of greenhouse gases and high-salt wastewater, reducing energy consumption and process steps, improving metal recovery and graphite utilization Rate.
Smart Images

Figure CN119430174A_ABST
Abstract
Description
Technical field:
[0001] The invention relates to the technical field of waste lithium battery wet leaching tailings disposal, and in particular to a method for flash evaporation purification of waste lithium battery graphite leaching residues. Background technology:
[0002] Waste lithium batteries include waste lithium iron phosphate batteries, waste ternary lithium batteries, waste lithium manganese oxide batteries and waste lithium cobalt oxide. The tailings of the black powder of the waste lithium batteries are leached by wet method, and then the metal salts are collected by flotation, and a large amount of low-value graphite leaching slag is discharged. This type of graphite leaching slag contains residual metals such as lithium, iron, sodium, copper and aluminum. Due to the high impurity content and lattice defects, it is directly used as a fuel for incineration, reduction roasting of metal oxides or high-temperature repair of graphite. In addition to releasing a large amount of CO2 during direct incineration, the sulfur, nitrogen or chloride remaining in the graphite leaching slag by wet leaching will generate corresponding oxides during incineration. In addition, reduction roasting requires a large amount of organic solvents to clean the graphite leaching slag attached to the metal compound, and high-temperature repair requires a long time of treatment at an ultra-high temperature of about 3000°C. Greenhouse gases, organic solvents and high-temperature energy consumption increase the economic cost of recycling graphite leaching slag and reduce the environmental benefits of graphite leaching slag, which requires more appropriate methods for further disposal. CN118060299B discloses a method for recycling graphite from the negative electrode of waste batteries, wherein the negative electrode graphite is finely ground and pre-treated to dissociate impurities, and then impurities are removed by acid leaching, and finally high-purity graphite is obtained by flotation. Although the recovery rate of graphite can exceed 97%, the acid leaching and impurity removal step will introduce more impurity elements into the graphite lattice, reducing the purity of graphite. CN109786739B discloses a method for recycling positive electrode materials of lithium batteries by using molten salt-assisted carbon thermal reduction, wherein calcium salt is hot-melted and cold-ground, mixed with lithium cobalt oxide and graphite, and then calcined at high temperature for not less than 0.5h and then magnetically separated to obtain cobalt element, and then sodium sulfate is used to remove calcium impurities and sodium carbonate is used to precipitate lithium. Although more than 93% of cobalt and not less than 85% of lithium are finally recovered, the lengthy impurity removal step and the introduction of multiple impurity elements greatly limit the metal recovery rate, reducing the recovery efficiency and graphite utilization rate.
[0003] Therefore, it is necessary to develop a high-efficiency, low-consumption, green and economical method for recovering graphite leaching slag. Summary of the invention:
[0004] The purpose of the present invention is to provide a method for flash distillation purification of waste lithium battery graphite leaching residue, which solves the problems of high recovery cost and energy consumption of graphite leaching residue discharged from waste lithium battery wet leaching, long residual metal recovery process and introduction of impurity elements.
[0005] The present invention is achieved through the following technical solutions:
[0006] A method for flash distillation purification of waste lithium battery graphite leaching residue, the method comprising the following steps:
[0007] (1) Flash halogenation: Mix the waste lithium battery graphite leaching residue and the halogenating agent and spread them on carbon paper, put them into a reaction chamber with an air inlet and an air outlet, adjust the gas in the reaction chamber to an argon environment, the pressure is 0.4MPa~1.05MPa, and the flash voltage density is 30V / cm 2 ~40V / cm 2 , the flash evaporation times are 1 to 6 times and the flash evaporation temperature is 1800° C. to 2300° C., and solid phase purified graphite and gas phase metal flash vapor are separated;
[0008] (2) Joule flash coating: The purified graphite obtained in step (1) is ground and mixed with asphalt, then wrapped with carbon paper, and then placed in a reaction chamber with an air inlet and an air outlet, and the gas environment pressure in the reaction chamber is adjusted to 0.3 MPa to 0.8 MPa, and the Joule heat insulation current density is 103 A / cm 2 ~105.5A / cm 2 , the Joule heat holding time is 6s to 7.2s and the Joule heat holding temperature is 762° C. to 769.5° C., to obtain a lithium battery negative electrode graphite material;
[0009] (3) Solid-gas lithium extraction: passing the metal flash vapor obtained in step (1) into a dilute acid solution to leach the lithium element, and filtering to obtain tailings and lithium-rich liquid;
[0010] (4) Lithium precipitation by explosive gasification: The lithium-rich solution obtained in step (3) is passed through explosive carbon dioxide and filtered to obtain lithium carbonate and water.
[0011] Preferably, the waste lithium battery graphite leaching slag is one of waste lithium iron phosphate battery black powder, waste ternary lithium battery black powder, waste lithium manganese oxide battery black powder and waste lithium cobalt oxide black powder recycled by the hydrometallurgical industry, and contains residual metals such as lithium, iron, sodium, copper and aluminum.
[0012] When the waste lithium battery graphite leaching residue is used for the hydrometallurgical industry to recycle the waste lithium iron phosphate battery black powder, the hydrometallurgical process uses nitric acid, sulfuric acid or hydrochloric acid, and the total content of metal elements lithium, iron, sodium, chromium, copper and aluminum in the graphite leaching residue of the waste lithium iron phosphate battery black powder is greater than 80ppm; when the waste lithium battery graphite leaching residue is used for the hydrometallurgical industry to recycle the waste ternary lithium battery black powder with strong acid, the hydrometallurgical process uses nitric acid, sulfuric acid or hydrochloric acid, and the total content of metal elements lithium, iron, sodium, chromium, nickel, cobalt, manganese, copper and aluminum in the graphite leaching residue of the waste ternary lithium battery black powder is greater than 90ppm; when the waste lithium battery graphite leaching residue is used for the hydrometallurgical industry to recycle the waste lithium manganese oxide battery black powder, the hydrometallurgical process uses nitric acid, sulfuric acid or hydrochloric acid, and the total content of the metal elements lithium, iron, sodium, manganese, copper and aluminum in the graphite leaching residue of the waste lithium manganese oxide battery black powder is greater than 80ppm; when the waste lithium battery graphite leaching residue is used for the hydrometallurgical industry to recycle the waste lithium cobalt oxide black powder, the hydrometallurgical process uses nitric acid, sulfuric acid or hydrochloric acid, and the total content of the metal elements lithium, iron, sodium, cobalt, copper and aluminum in the graphite leaching residue of the waste lithium cobalt oxide battery black powder is greater than 80ppm.
[0013] Preferably, the halogenating agent in step (1) is one of NaCl, NH4Cl, KCl, NaI, NH4I, and KI.
[0014] Preferably, the mass ratio of the halogenating agent in step (1) to the waste lithium battery graphite leaching residue is 1:80 g / g to 1:180 g / g, more preferably 1:100 g / g to 1:160 g / g, and optimally 1:120.
[0015] Preferably, the carbon paper area in step (1) is 80 m 2 / kg~480m 2 / kg, more preferably 160m 2 / kg~400m 2 / kg, the most preferred is 240m 2 / kg~320m 2 / kg.
[0016] Preferably, in step (1), the gas environment pressure in the reaction chamber is adjusted to 0.55 MPa to 0.9 MPa, and the flash voltage density is 32 V / cm 2 ~38V / cm 2 , the number of flash evaporation times is 2 to 5 times and the flash evaporation temperature is 1900°C to 2200°C.
[0017] Preferably, in step (2), the purified graphite obtained in step (1) is washed with deionized water for multiple times until it is neutral and then dried, then ground and mixed with asphalt and wrapped with carbon paper, and the mass ratio of purified graphite to asphalt is adjusted to 4:1-1.5:1 g / g, the gas environment of the reaction chamber is nitrogen, the pressure is 0.4-0.7 MPa, and the Joule heat insulation current density is 103.5 A / cm2 ~105A / cm 2 The Joule heat holding time is 6.2s~7s, and the Joule heat holding temperature is 763.5℃~768℃.
[0018] Preferably, the flow rate of the metal flash gas introduced in step (3) is 19 mL / s to 24 mL / s, the dilute acid solution is 0.01 M to 0.25 M dilute hydrochloric acid, and the mechanical stirring speed is 500 rpm to 600 rpm.
[0019] Preferably, step (4) is as follows: in step (3), the lithium-rich liquid is introduced into CO2 through an explosion disk at a low temperature of 2°C to 7°C, and the carbon charging capacity of the explosion disk is 0.05kg CO2 / h to 0.15kg CO2 / h.
[0020] Compared with the prior art, the present invention has the following advantages:
[0021] 1. Compared with the conventional methods of recycling waste graphite or graphite leaching residue by acid leaching for impurity removal, high temperature roasting for metal recovery, long-term high temperature repair and the like, the flash halogenation in step (1) of the present invention uses Joule heat flash halogenation to treat the graphite leaching residue and a mixture of cheap halide salts, thereby achieving metal impurity removal and graphite structure repair instantly and simultaneously. The Joule heat flash evaporation temperature of the impurity metal halide is greatly reduced by utilizing the low boiling point of the halide salt. The purified graphite obtained has high purity, complete structure, and contains only trace amounts of impurity elements. It has the advantages of rapid reaction time, short process, no introduction of impurity elements, and high degree of graphitization.
[0022] 2. The surface kinetic energy generated in the Joule heat insulation state in step (2) of the present invention drives the asphalt particles to be coated on the surface of the purified graphite particles, avoiding the defects of the traditional coating process such as furan chemical impregnation, long stirring time, and large material loss. The coated graphite negative electrode can be directly used as a negative electrode material for lithium-ion batteries.
[0023] 3. Lithium precipitation by explosive gasification under low temperature conditions avoids the disadvantages of low purity of lithium carbonate caused by traditional processes of lithium precipitation using sodium carbonate or carbon dioxide. It uses low-temperature explosive gasification to carbonize lithium carbonate into lithium bicarbonate and then adjusts the temperature to precipitate lithium carbonate. The obtained lithium carbonate product has high purity and can be directly used as a lithium source in lithium battery positive electrode materials, which has excellent industrial application potential.
[0024] In summary, the present invention uses Joule heat high-temperature gasification flash evaporation of impurity metals in waste lithium battery graphite leaching residue to achieve simultaneous deep impurity removal of metals and graphite lattice structure repair, replacing traditional multi-step processes such as acid leaching, multi-step impurity removal and long-term high temperature. The graphite purity is as high as 99.7%, and the lithium carbonate purity is as high as 99.5%. It not only avoids the large-scale discharge of greenhouse gases and high-salt wastewater, but also directionally refines and purifies the impurity metals into battery-grade lithium carbonate materials, providing an efficient, green and economical closed-loop disposal method and high-value utilization method for the disposal of waste lithium battery graphite leaching residue and battery-grade precursors. Description of the drawings:
[0025] Figure 1 This is the XRD diagram of the lithium battery negative electrode graphite material obtained in Example 5 of the present invention.
[0026] Figure 2 This is the TEM image of the lithium battery negative electrode graphite material obtained in Example 5 of the present invention. Specific implementation method:
[0027] The following is a further description of the present invention, rather than a limitation of the present invention.
[0028] Example 1: A method for flash purification of waste lithium battery graphite leaching residue
[0029] The steps include:
[0030] (1) Flash halogenation: The halogenating agent NaCl and the graphite leaching residue of the waste ternary lithium battery black powder recovered by the hydrometallurgical industrial strong acid process (the total content of metal elements lithium, iron, sodium, chromium, nickel, cobalt, manganese, copper and aluminum in the graphite leaching residue of the waste ternary lithium battery black powder is greater than 90 ppm) are mixed in a mass ratio of 1:80 g / g and placed on carbon paper with an area of 80 m 2 / kg, put it into a reaction chamber with an air inlet and an air outlet, adjust the argon pressure of the reaction chamber gas environment to 0.4MPa, and the flash voltage density to 30V / cm 2 , the number of times is 1, the flash evaporation temperature is 1800℃, and the solid phase purified graphite and the gas phase metal flash gas are separated.
[0031] (2) Joule flash coating: The purified graphite obtained in step (1) was washed with deionized water for several times until it was neutral and then dried, ground and mixed with asphalt and then wrapped with carbon paper, the mass ratio of purified graphite to asphalt being 4:1 g / g, and placed in a reaction chamber with an air inlet and an air outlet, and the nitrogen pressure of the reaction chamber environment was adjusted to 0.3 MPa, and the Joule thermal insulation current density was 103 A / cm 2 The Joule heat holding time is 6s, the Joule heat holding temperature is 762°C, and a lithium battery negative electrode graphite material is obtained.
[0032] (3) Solid-gas lithium extraction: The metal flash vapor obtained in step (1) is introduced into dilute hydrochloric acid, the metal flash vapor flow rate is 19 mL / s, the dilute hydrochloric acid concentration is 0.01 M, the mechanical stirring speed is 500 rpm, and the tailings and lithium-rich liquid are obtained by filtration.
[0033] (4) Low-temperature explosion and lithium precipitation: The lithium-rich liquid obtained by filtration in step (3) is introduced into CO2 through an explosion disk at a low temperature of 2°C. The carbon charging capacity of the explosion disk is 0.05 kg CO2 / h. Lithium carbonate and water are obtained by filtration.
[0034] Example 2: A method for flash purification of waste lithium battery graphite leaching residue
[0035] The steps include:
[0036] (1) Flash halogenation: The halogenating agent KI and the graphite leaching residue from the hydrometallurgical industrial strong acid process to recover the waste ternary lithium battery black powder were mixed at a mass ratio of 1:180 g / g and placed on carbon paper with an area of 480 m 2 / kg, put it into a reaction chamber with an air inlet and an air outlet, adjust the argon pressure of the reaction chamber gas environment to 1.05MPa, and the flash voltage density to 40V / cm 2 , the number of times is 6 times, the flash evaporation temperature is 2300℃, and solid phase purified graphite and gas phase metal flash vapor are separated.
[0037] (2) Joule flash coating: The purified graphite obtained in step (1) was washed with deionized water for multiple times until neutral and then dried, ground and mixed with asphalt and then wrapped with carbon paper, the mass ratio of purified graphite to asphalt being 1.5:1 g / g, and placed in a reaction chamber with an air inlet and an air outlet, and the nitrogen pressure of the reaction chamber environment was adjusted to 0.8 MPa, and the Joule thermal insulation current density was 105.5 A / cm 2 The Joule heat holding time is 7.2s, the Joule heat holding temperature is 769.5℃, and the lithium battery negative electrode graphite material is obtained.
[0038] (3) Solid-gas lithium extraction: The metal flash vapor obtained in step (1) is introduced into dilute hydrochloric acid, the metal flash vapor flow rate is 24 mL / s, the dilute hydrochloric acid concentration is 0.25 M, the mechanical stirring speed is 600 rpm, and the tailings and lithium-rich liquid are obtained by filtration.
[0039] (4) Low-temperature explosion and lithium precipitation: The lithium-rich liquid obtained by filtration in step (3) is introduced into CO2 through an explosion disk at a low temperature of 7°C. The carbon charging capacity of the explosion disk is 0.15 kg CO2 / h. Lithium carbonate and water are obtained by filtration.
[0040] Example 3: A method for flash purification of waste lithium battery graphite leaching residue
[0041] The steps include:
[0042] (1) Flash halogenation: The halogenating agent NH4Cl and the graphite leaching residue from the recycling of waste ternary lithium battery black powder by the hydrometallurgical industrial strong acid process were mixed at a mass ratio of 1:100 g / g and placed on carbon paper with an area of 160 m 2 / kg, put it into a reaction chamber with an air inlet and an air outlet, adjust the argon pressure of the reaction chamber gas environment to 0.55MPa, and the flash voltage density to 32V / cm 2 , the number of times is 2 times, the flash evaporation temperature is 1900℃, and the solid phase purified graphite and gas phase metal flash vapor are separated.
[0043] (2) Joule flash coating: The purified graphite obtained in step (1) was washed with deionized water for multiple times until neutral and then dried, ground and mixed with asphalt and then wrapped with carbon paper, the mass ratio of purified graphite to asphalt being 3.5:1 g / g, and placed in a reaction chamber with an air inlet and an air outlet, and the nitrogen pressure of the reaction chamber environment was adjusted to 0.4 MPa, and the Joule thermal insulation current density was 103.5 A / cm 2 The Joule heat holding time is 6.2s, the Joule heat holding temperature is 763.5℃, and the lithium battery negative electrode graphite material is obtained.
[0044] (3) Solid-gas lithium extraction: The metal flash vapor obtained in step (1) is introduced into dilute hydrochloric acid at a metal flash vapor flow rate of 20 mL / s, a dilute hydrochloric acid concentration of 0.05 M, and a mechanical stirring speed of 520 rpm. The tailings and lithium-rich liquid are filtered out.
[0045] (4) Low-temperature explosion and lithium precipitation: The lithium-rich liquid obtained by filtration in step (3) is introduced into CO2 through an explosion disk at a low temperature of 3°C. The carbon charging capacity of the explosion disk is 0.07 kg CO2 / h. Lithium carbonate and water are obtained by filtration.
[0046] Example 4: A method for flash purification of waste lithium battery graphite leaching residue
[0047] The steps include:
[0048] (1) Flash halogenation: The halogenating agent NH4I and the graphite leaching residue from the recycling of waste ternary lithium battery black powder by the hydrometallurgical industrial strong acid process were mixed at a mass ratio of 1:160 g / g and placed on carbon paper with an area of 400 m 2 / kg, put it into a reaction chamber with an air inlet and an air outlet, adjust the argon pressure of the reaction chamber gas environment to 0.9MPa, and the flash voltage density to 38V / cm 2 , the number of times is 5 times, the flash evaporation temperature is 2200℃, and solid phase purified graphite and gas phase metal flash vapor are separated.
[0049] (2) Joule flash coating: The purified graphite obtained in step (1) was washed with deionized water for several times until it was neutral and then dried, ground and mixed with asphalt and then wrapped with carbon paper, the mass ratio of purified graphite to asphalt being 2:1 g / g, and placed in a reaction chamber with an air inlet and an air outlet, and the nitrogen pressure of the reaction chamber environment was adjusted to 0.7 MPa, and the Joule thermal insulation current density was 105 A / cm 2 The Joule heat holding time is 7s, the Joule heat holding temperature is 768°C, and the lithium battery negative electrode graphite material is obtained.
[0050] (3) Solid-gas lithium extraction: The metal flash vapor obtained in step (1) is introduced into dilute hydrochloric acid at a metal flash vapor flow rate of 23 mL / s, a dilute hydrochloric acid concentration of 0.2 M, and a mechanical stirring speed of 580 rpm. The tailings and lithium-rich liquid are filtered out.
[0051] (4) Low-temperature explosion and lithium precipitation: The lithium-rich liquid obtained by filtration in step (3) is introduced into CO2 through an explosion disk at a low temperature of 6°C. The carbon charging capacity of the explosion disk is 0.13 kg CO2 / h. Lithium carbonate and water are obtained by filtration.
[0052] Example 5: A method for flash purification of waste lithium battery graphite leaching residue
[0053] The steps include:
[0054] (1) Flash halogenation: The halogenating agent KCl and the graphite leaching residue from the hydrometallurgical industrial strong acid process to recover the waste ternary lithium battery black powder were mixed at a mass ratio of 1:120 g / g and placed on carbon paper with an area of 240 m 2 / kg, put it into a reaction chamber with an air inlet and an air outlet, adjust the argon pressure of the reaction chamber gas environment to 0.6MPa, and the flash voltage density to 34V / cm 2 , the number of times is 3 times, the flash evaporation temperature is 2000℃, and solid phase purified graphite and gas phase metal flash vapor are separated.
[0055] (2) Joule flash coating: The purified graphite obtained in step (1) was washed with deionized water for several times until it was neutral and then dried, ground and mixed with asphalt and then wrapped with carbon paper, the mass ratio of purified graphite to asphalt being 3:1 g / g, and placed in a reaction chamber with an air inlet and an air outlet, and the nitrogen pressure of the reaction chamber environment was adjusted to 0.5 MPa, and the Joule thermal insulation current density was 104 A / cm 2 The Joule heat holding time is 6.4s, the Joule heat holding temperature is 765℃, and the lithium battery negative electrode graphite material is obtained. Its XRD pattern is shown in Figure 1 , its TEM image is shown in Figure 2 .
[0056] (3) Solid-gas lithium extraction: The metal flash vapor obtained in step (1) is introduced into dilute hydrochloric acid at a metal flash vapor flow rate of 21 mL / s, a dilute hydrochloric acid concentration of 0.1 M, and a mechanical stirring speed of 540 rpm. The tailings and lithium-rich liquid are filtered out.
[0057] (4) Low-temperature explosion and lithium precipitation: The lithium-rich liquid obtained by filtration in step (3) is introduced into CO2 through an explosion disk at a low temperature of 4°C. The carbon charging capacity of the explosion disk is 0.09 kg CO2 / h. Lithium carbonate and water are obtained by filtration.
[0058] Example 6: A method for flash purification of waste lithium battery graphite leaching residue
[0059] The steps include:
[0060] (1) Flash halogenation: The halogenating agent NaI and the graphite leaching residue from the hydrometallurgical industrial strong acid process to recover the waste ternary lithium battery black powder were mixed at a mass ratio of 1:140 g / g and placed on carbon paper with an area of 320 m 2 / kg, put it into a reaction chamber with an air inlet and an air outlet, adjust the argon pressure of the reaction chamber gas environment to 0.75MPa, and the flash voltage density to 36V / cm 2 , the number of times is 4 times, the flash evaporation temperature is 2100℃, and solid phase purified graphite and gas phase metal flash vapor are separated.
[0061] (2) Joule flash coating: The purified graphite obtained in step (1) was washed with deionized water for multiple times until neutral and then dried, ground and mixed with asphalt and then wrapped with carbon paper, the mass ratio of purified graphite to asphalt being 2.5:1 g / g, and placed in a reaction chamber with an air inlet and an air outlet, the nitrogen pressure of the reaction chamber environment was adjusted to 0.6 MPa, and the Joule thermal insulation current density was 104.5 A / cm 2 The Joule heat holding time is 6.8s, the Joule heat holding temperature is 766.5℃, and the lithium battery negative electrode graphite material is obtained.
[0062] (3) Solid-gas lithium extraction: The metal flash vapor obtained in step (1) is introduced into dilute hydrochloric acid at a metal flash vapor flow rate of 22 mL / s, a dilute hydrochloric acid concentration of 0.15 M, and a mechanical stirring speed of 560 rpm. The tailings and lithium-rich liquid are filtered out.
[0063] (4) Low-temperature explosion and lithium precipitation: The lithium-rich liquid obtained by filtration in step (3) is introduced into CO2 through an explosion disk at a low temperature of 5°C. The carbon charging capacity of the explosion disk is 0.11 kg CO2 / h. Lithium carbonate and water are obtained by filtration.
[0064] Comparative Example 1: A method for flash purification of waste lithium battery graphite leaching residue
[0065] Refer to Example 2, the difference is that the gas environment of the reaction chamber in the flash halogenation process in step (1) is nitrogen, and the rest of the process and parameters are the same as Example 2.
[0066] Since argon gas was not filled in the flash halogenation process in Comparative Example 1, nitrogen was ionized at an instantaneous high temperature and formed a complex nitrogen-containing gas with impurity elements, resulting in an increase in impurity products. In addition, an additional process was required for impurity removal for solid-gas lithium extraction, and nitrogen-containing organic compounds adhered to the surface of the purified graphite, resulting in an additional impurity removal process, which failed to achieve the problem of efficient disposal of waste lithium battery graphite leaching residue.
[0067] Comparative Example 2: A method for flash purification of waste lithium battery graphite leaching residue
[0068] Refer to Example 2, the difference is that the Joule flash coating process in step (2) adopts flash evaporation voltage density and does not use Joule heat insulation current density. The rest of the process and parameters are the same as Example 2.
[0069] Since the Joule heat insulation current density was not used in Comparative Example 2, the flash evaporation voltage density was adopted, and the low-temperature heating time was very short, the asphalt did not completely cover the purified graphite, and there was obvious stratification between the asphalt and the graphite. In addition, the first-circuit coulomb efficiency was low, which basically met the standards for lithium-ion battery negative electrode materials and failed to achieve high-quality utilization of waste lithium battery graphite leaching residue.
[0070] The graphite purity, total residual amount of impurity elements, lithium carbonate purity and first coulomb efficiency in Examples 1 to 6 and Comparative Examples 1 to 2 are shown in Table 1:
[0071] Table 1
[0072]
[0073] The description of the above embodiments is only used to help understand the technical solution and core ideas of the present invention. It should be pointed out that for technicians in this technical field, several improvements and modifications can be made to the present invention without departing from the principles of the present invention. These improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. A method for flash purification of waste lithium battery graphite leaching residue, characterized in that: The method comprises the following steps: (1) Flash halogenation: Mix the waste lithium battery graphite leaching residue and the halogenating agent and spread them on carbon paper, put them into a reaction chamber with an air inlet and an air outlet, adjust the gas in the reaction chamber to an argon environment, the pressure is 0.4MPa~1.05MPa, and the flash voltage density is 30V / cm 2 ~40V / cm 2 , the flash evaporation times are 1 to 6 times and the flash evaporation temperature is 1800° C. to 2300° C., and solid phase purified graphite and gas phase metal flash vapor are separated; (2) Joule flash coating: The purified graphite obtained in step (1) is ground and mixed with asphalt, then wrapped with carbon paper, and then placed in a reaction chamber with an air inlet and an air outlet, and the gas environment pressure in the reaction chamber is adjusted to 0.3 MPa to 0.8 MPa, and the Joule heat insulation current density is 103 A / cm 2 ~105.5A / cm 2 , the Joule heat holding time is 6s to 7.2s and the Joule heat holding temperature is 762° C. to 769.5° C., to obtain a lithium battery negative electrode graphite material; (3) Solid-gas lithium extraction: passing the metal flash vapor obtained in step (1) into a dilute acid solution to leach the lithium element, and filtering to obtain tailings and lithium-rich liquid; (4) Lithium precipitation by explosive gasification: The lithium-rich solution obtained in step (3) is passed through explosive carbon dioxide and filtered to obtain lithium carbonate and water.
2. The method according to claim 1, characterized in that The waste lithium battery graphite leaching slag is one of the waste lithium iron phosphate battery black powder, waste ternary lithium battery black powder, waste lithium manganese oxide battery black powder and waste lithium cobalt oxide black powder recycled by the hydrometallurgical industry, and contains lithium, iron, sodium, copper and aluminum.
3. The method according to claim 1 or 2, characterized in that: The halogenating agent in step (1) is one of NaCl, NH4Cl, KCl, NaI, NH4I and KI.
4. The method according to claim 1 or 2, characterized in that: Step (1) The mass ratio of the halogenating agent to the waste lithium battery graphite leaching residue is 1:80g / g to 1:180g / g, and the carbon paper area is 80m 2 / kg~480m 2 / kg.
5. The method according to claim 1 or 2, characterized in that: Step (1) The mass ratio of the halogenating agent to the waste lithium battery graphite leaching residue is 1:100 g / g to 1:160 g / g, and the carbon paper area is 160 m 2 / kg~400m 2 / kg.
6. The method according to claim 1 or 2, characterized in that: Step (1) The mass ratio of the halogenating agent to the waste lithium battery graphite leaching residue is 1:120, and the carbon paper area is 240m 2 / kg~320m 2 / kg.
7. The method according to claim 1 or 2, characterized in that: Step (1) Adjust the gas environment pressure in the reaction chamber to 0.55MPa-0.9MPa and the flash voltage density to 32V / cm 2 ~38V / cm 2 , the number of flash evaporation times is 2 to 5 times and the flash evaporation temperature is 1900°C to 2200°C.
8. The method according to claim 1 or 2, characterized in that: Step (2) The purified graphite obtained in step (1) is washed with deionized water for multiple times until it is neutral and then dried, then ground and mixed with asphalt and wrapped with carbon paper, the mass ratio of purified graphite to asphalt is adjusted to 4:1-1.5:1 g / g, the reaction chamber gas environment is nitrogen, the pressure is 0.4-0.7 MPa, and the Joule heat insulation current density is 103.5 A / cm 2 ~105A / cm 2 The Joule heat holding time is 6.2s~7s, and the Joule heat holding temperature is 763.5℃~768℃.
9. The method according to claim 1 or 2, characterized in that: In step (3), the flow rate of the metal flash vapor is 19 mL / s to 24 mL / s, the dilute acid solution is 0.01 M to 0.25 M dilute hydrochloric acid, and the mechanical stirring speed is 500 rpm to 600 rpm.
10. The method according to claim 1 or 2, characterized in that: Step (4) is as follows: the lithium-rich liquid in step (3) is introduced into CO2 through an explosion disk at a low temperature of 2°C to 7°C, and the carbon charging capacity of the explosion disk is 0.05kg CO2 / h to 0.15kg CO2 / h.
Citation Information
Patent Citations
A method for recovering lithium battery cathode materials by molten salt-assisted carbothermic reduction
CN109786739B
A method for recycling graphite from waste battery negative electrodes
CN118060299B
Cited By
Method for recovering lithium metal in waste all-solid-state lithium metal battery by Joule thermal method
CN121362883A
A method for upgrading waste graphite negative electrode to fast-charging graphite based on joule heat technology
CN122853378A